HUBUNGAN ANTARA WAKTU TUNGGU PELAYANAN RESEP NON RACIKAN DENGAN KEPUASAN PASIEN DI INSTALASI FARMASI PUSKESMAS CIKAMPEK UTARA - Maya Arfania; Desy Nur Fauziah; Lina Aliyani Mardiana (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2022)
Quality services will make patients feel satisfied. Patients will feel satisfied when they get services according to their needs and perceptions. Preliminary study regarding the level of patient satisfaction with waiting times for non-concoction prescription services, and it was found that 70% of patients were dissatisfied with the length of the waiting time. The purpose of this study was to determine the level of patient satisfaction with non-concoction prescription services and to analyze the relationship between waiting time for non-concoction prescription services and the level of satisfaction at the pharmacy installation of the North Cikampek Public Health Center. This research is an observational analytic study where data collection is done prospectively. The number of samples is 100 patients. The results in this study were mostly dissatisfied with 46 patients (46%). There is a relationship between waiting time for non-concoction prescription services and the level of satisfaction at the North Cikampek Public Health Center with a p-value of 0.000 (<0.05).